How doctors make themselves understood in primary care consultations: A mixed methods analysis of video data applying health literacy universal precautions. - Jennifer V Byrne (Public Library of Science (PLoS), 2021)
Purpose To mitigate the health risks that result from low health literacy and difficulty identifying patients with insufficient health literacy, health organizations recommend physicians apply health literacy universal precaution communication skills when communicating with all patients. Our aim was to assess how health literacy universal precautions are delivered in routine GP consultations, and explore whether there were differences in how GPs used universal precaution approaches according to areas of deprivation in England. Methods This was a mixed methods study using video and interview data. Ten physicians conducted 217 consultations in primary care settings with adults over 50 years old between July 2017 and March 2018 in England. Eighty consultations (N = 80) met the inclusion criteria of new or persisting problems. Descriptive quantitative analysis of video-recorded consultations using an observation tool and qualitative thematic analysis of transcribed scripts. Meta-themes explored differences in physicians' communication by areas of deprivation. Results Descriptive statistics showed physicians used a caring tone of voice and attitude (n = 73, 91.3%) and displayed comfortable body language (n = 69, 86.3%) but infrequently demonstrated profession-specific health literacy universal precaution communication skills, such as the teach-back technique (n = 3, 3.8%). Inferences about physicians' communication from qualitative analysis converged with the quantitative findings. Differences in physicians' communication varied according to areas of deprivation. Conclusions Physicians need health literacy universal precautions communication skills to improve population health.